Women’s Empowerment Through Collateral-Free Credit (Case Study of the An-Nisa Pati Cooperative) - Zunaida, Daris; Endang Suswati; Sugeng Mulyono; Jamal Abdul Nasir (Journal of Islamic Economic Studies, 2025)
Women's empowerment is a top priority in Indonesia's economic development, aligned with the Sustainable Development Goals (SDGs), particularly SDG 5 on gender equality and SDG 8 on economic growth and decent work. However, women still face significant barriers in accessing formal financing. This study aims to analyze the role of the An-Nisa Pati Cooperative as a local institutional innovation in providing access to collateral-free microcredit and its impact on women's economic empowerment. The research method used a descriptive qualitative approach with in-depth interviews, participant observation, and document analysis. The results show that the An-Nisa Cooperative not only opens access to financing for women in microenterprises, agriculture, and informal businesses, but also increases women's self-confidence, social solidarity, and economic participation. The implications of this study emphasize the importance of strengthening community-based institutions as an effective strategy to address structural inequalities and promote gender mainstreaming in local economic development.